Dosimetric comparison of multiple vs single isocenter technique for linear accelerator‐based stereotactic radiosurgery: The Importance of the six degree couch. Issue 6 (21st May 2021) - Amaya, Dania; Shinde, Ashwin; Wohlers, Christopher; Wong, Ka Chun Carson; Novak, Jennifer; Neylon, John; Han, Chunhui; Liu, An; Dandapani, Savita; Glaser, Scott
Abstract: Purpose: S ingle isocenter technique (SIT) for linear accelerator‐based stereotactic radiosurgery (SRS) is feasible. However, SIT introduces the potential for rotational error which can lead to geographical miss. Additional planning treatment volume (PTV) margin is required when using SIT. With the six degrees of freedom (6DoF) couch, rotational error can be minimized. We sought to evaluate the effect of the 6DoF couch on the dosimetry of patients with multiple brain metastases treated with SIT. Materials and Methods: Ten consecutive patients treated with SRS to ≥3 metastases were identified. Original treatments had MIT plans (MITP). The lesions were replanned using SIT. Lesions 5‐10 cm from isocenter had an additional 1mm of margin. Patients were replanned with these additional margins to account for inability to correct rotational error (SITPM). Multiple dosimetric variables and time metrics were evaluated. Dosimetry planning time (DPT) and patient treatment time (PTT) were evaluated. Statistics were calculated using the Wilcoxon signed‐rank test. Results: A total of 73 brain metastases receiving SRS, to a median of 6 lesions per patient, were identified. MITPs treated 73 lesions with 63 isocenters. On average, MITPs had a 19.2% higher brain V12 than SITPs ( P = 0.017). For creation of SITPM, 30 lesions required 1 mm of additional margin, while none required 2 mm of margin. This increased V12 by 47.8% on average per patient ( P = 0.008) from SITP to SITPM. DPT was 5.5 hours for SITP, while median for MITP was 12.5 hours ( P = 0.005) PTT was 30 minutes for SITP, while median for MITP was 144 minutes ( P = 0.005). Conclusions: SITPs are comparable to MITPs if rotational error can be corrected with the use of a 6DoF couch. Increasing margin to account for rotational error leads to a nearly 50% increase in V12, which could result in higher rates of radiation necrosis. Time savings are significant using SIT.